Response of concentrate supplementation on ovulation rate and progesterone receptor gene in goats - Mohammed, Nur Hafizah (2018)
Nutritional supplementations on reproductive performance such as ovulation rate and embryo survival in sheep are well-documented, but there are still debates among researchers and farmers regarding this matter in goats. In goats, there were some evidences shown that high energy/protein supplementation does not promotes an increment on ovulation rate, but able to sustain the embryo survivability, thus maintain the pregnancy. Therefore, this study was conducted to examine the effect of short-term supplementation of concentrate (commercial concentrate; double maintenance) on size of ovary and corpus luteum (CL), ovulation rate in relation to live weight, body condition score (BCS) and changes of physiological parameter of the ovary and CL. Also, to determine the effects of protein supplement on mRNA expression of progesterone receptor (PR) gene, thus specific primer for PR gene was designed to qualify the presence of PR expression. In this study, 17 of female Boer goats were divided into two groups; 1) Control group received maintenance diet (commercial concentrate and Napier grass) and 2) Treatment Group received double maintenance diet (commercial concentrate-2M and Napier grass). The feeding treatment was started 5 days prior to CIDR removal (Day 0) for 25 days. On Day 19, ovaries were examined by ultrasound and ovulation rate were calculated by presence number of CL. The live weight and BCS were recorded every two weeks until animals were slaughtered (Day 27), the number and diameter of removed ovary and CL were measured. Results from this study demonstrated that short-term supplementation of concentrate had no effect on ovulation rate (Control = 1.00 ± 0.2; Treated = 1.25 ± 0.2; p>0.05) and no changes in live weight and BCS were observed throughout the experiment. In addition, in both Groups revealed that size of ovary does not correlated with size CL. We suggest that effect of concentrate supplementation inducing ovulation is relatively weaker in goats compared to sheep. This might be due to low amount of energy level to enhance the ovulation rate. However, present results showed that the does treated with double maintenance of commercial concentrate able to influence the expression of PR gene in ovaries tissue. The expression of PR gene in supplemented goats was increased by 3.7 fold in CL and 2.3 fold in follicles tissue (p<0.05). Surprisingly, present result indicated that they expression of PR gene between left and right CLs was similar between groups. Hence, concentrate supplementation could promote growth and development of high quality predominant follicles and thus fully functional CL will be produced. We suggest that, concentrate supplementation is able to maintain the structural and functional integrity of CL tissue, thus production of progesterone concentration may not be affected. In this study, we concluded that concentrate supplementation are not able to increase ovulation rate of female goats but the supplement able to maintain the structural and function of CL tissue.